Persaingan Daya Tarik BBM Dikalangan Masyarakat Antara PT. Pertamina Indonesia Dan Petronas Malaysia (Studi Kasus Indonesia Dengan Malaysia) - Asti Peggy Aliyantie; Afif Husain Yasir; Maura Putri Alicia; Salya Prayoga; Daspar (Jurnal Ekonomi dan Bisnis Digital, 2024)
This analysis aims to determine the public's interest in comparing services, quality, price and which fuel is more efficient. Does the public remain loyal to one of these fuels? This research uses a descriptive method, where phenomena occur among society. These phenomena can take the form of activities, characteristics, changes, relationships, similarities and differences. Gas stations should maintain existing services in accordance with their SOP.